Alternative Sampling Devices to Collect Dried Blood Microsamples: State-of-the-Art - Delahaye, Lisa; Veenhof, Herman; Koch, Birgit C P; Alffenaar, Jan-Willem C; Linden, Rafael; Stove, Christophe (Therapeutic drug monitoring, 2021)
Dried blood spots (DBS) have been used in newborn screening programs for several years. More recently, there has been growing interest in using DBS as a home sampling tool for the quantitative determination of analytes. However, this presents challenges, mainly because of the well-known hematocrit effect and other DBS-specific parameters, including spotted volume and punch site, which could add to the method uncertainty. Therefore, new microsampling devices that quantitatively collect capillary dried blood are continuously being developed. In this review, we provided an overview of devices that are commercially available or under development that allow the quantitative (volumetric) collection of dried blood (-based) microsamples and are meant to be used for home or remote sampling. Considering the field of therapeutic drug monitoring (TDM), we examined different aspects that are important for a device to be implemented in clinical practice, including ease of patient use, technical performance, and ease of integration in the workflow of a clinical laboratory. Costs related to microsampling devices are briefly discussed, because this additionally plays an important role in the decision-making process. Although the added value of home sampling for TDM and the willingness of patients to perform home sampling have been demonstrated in some studies, real clinical implementation is progressing at a slower pace. More extensive evaluation of these newly developed devices, not only analytically but also clinically, is needed to demonstrate their real-life applicability, which is a prerequisite for their use in the field of TDM.